Pendidikan Kebersihan dalam Perspekif hadis - Muinudin; Jaenudin, Agung (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2024)
Abstract. The main objective of this study is to review and analyze the traditions related to hygiene instructions. The research methodology employed in this study involves the use of a qualitative approach, specifically focusing on literature review. The objective was to analyze and understand the traditions related to hygiene instructions through content analysis of the traditions. The study includes the results and subsequent analysis of the investigation conducted. 1) The concepts of education and hygiene can be defined as follows: Education refers to the process of acquiring knowledge, skills, values, and attitudes through various formal and informal means, while hygiene pertains to practices and behaviors aimed at maintaining cleanliness and promoting health. 2) When examining hygiene education from the perspective of hadith, which are the words and actions of the Prophet Muhammad (pbuh), it is clear that cleanliness and hygiene have great importance. The hadith literature contains many teachings that emphasize the importance of cleanliness, both in terms of physical hygiene and spiritual purity. These teachings serve as a guide for individuals who wish to maintain cleanliness. 3) Hadiths related to cleanliness. In this study, it can be concluded that maintaining cleanliness requires awareness in each individual, both inner, spiritual and environmental cleanliness. This research aims to provide Keywords: Education, Cleanliness, Hadiths of Cleanliness